The Cold War and Educational Exchanges: The Origins of the Fulbright Program in Portugal - Rodrigues, L. N. (Cultural Diplomacy in Southern Europe: Spain, Portugal and Greece in the Twentieth Century, 2026)
This chapter examines the establishment of the Fulbright Program in Portugal, contextualising its creation in 1960 within the broader framework of the Cold War and Portugal’s gradual integration into the sphere of influence of the United States. The text is divided into four sections. The first section explores Portugal’s geopolitical positioning and strategic significance during the Cold War, highlighting its integration into US-led initiatives such as NATO. The second focuses on the early educational exchanges between Portugal and the United States, which were limited by Portugal’s authoritarian regime and its cultural orientation towards Europe rather than the United States. The third section analyses the United States’ cultural and educational diplomacy efforts in Portugal during the early 1950s, emphasising the role of the Embassy and its cultural attaché, as well as targeted initiatives aimed at fostering cultural exchanges. Finally, this chapter traces the origins of, and the negotiations leading to, the signing of the Fulbright agreement, underscoring the agreement’s aim of promoting American values in Portugal through educational exchanges.